Particle distribution method for the homologous collapse of a sphere (2022)
In this work the adiabatic collapse of a sphere is studied. self-gravitating through a computational simulationcarried out with Gadget-2. This package has a simulation archetype for the homologous collapse of a unitsphere, which is represented by a series of concentric spherical shells, where the particles are equidistantlydistributed to represent a density ρ ~ r2. Another method has been created based on considering the unitsphere made up of small spheres inside. The problem comes down to packing the small spheres in the bestpossible way. This problem has been solved in solid state physics. For spherical symmetry, the maximumpacking factor is given by an FCC-type Bravais structure. In this work it is shown that the Gadget archetypeis equivalent to a CS structure that has a smaller packing factor. Consequently, the best way to represent agas sphere computationally is by means of an FCC distribution.